ESTUDO DO BAGAÇO DE MANDIOCA (Manihot esculenta C.), NATIVO E TRATADO COM α – AMILASE E AMILOGLUCOSIDASE, POR MEIO DE TÉCNICAS TERMOANALÍTICAS - (:unkn) unknown (UNIVERSIDADE ESTADUAL DE PONTA GROSSA, 2009)
Waste generation represent a daily problem for most of the agriculture industry due to its toxicity and/or volume produced. Nowadays these residues demands treatment before its discard in the environment. Besides, the amounts spent with treatment are aggregated to manufacturing costs. Rational use of the residues seems to be the best way to handle with this problem. Cassava roots processing industry, produces significant amount of solid and liquid wastes from which valuable products could be extracted. Cassava bagasse is one of these residues containing high amounts of starch and dietary fibers. Before processing, the starch, through amylolitic enzyme digestion yields glucose and maltose syrups, products with wide uses in industry, for example, brewing industry. Classic laboratory analyses were already used in the characterization of cassava bagasse, but too much time were necessary to obtain results. Hence the present study aims for the analysis of cassava bagasse from multiple ways, being the thermal analysis the most important of all. The thermal techniques employed were thermogravimetry (TG), differential thermal analysis (DTA), derivate thermogravimetry (DTG) and differential scanning calorimetry (DSC). As in other past studies, optic microscopy proved its use in the identification of this kind of sample. X ray powder diffractometry is classically employed in the study of semi-cristalinity starch granule structure and was used to analyze the cassava bagasse. When a hydrolytic process is applied to starchy material, significant amount of reducing sugars are produced. Dinitrosalicylic acid (DNS) reducing reaction was performed in the hydrolyzed liquid fraction. The degradation temperatures obtained through thermogravimetric analysis of the native and hydrolyzed solid fractions of the cassava bagasse suffer reduction as well as changes in enthalpy and combustion values were noticed. DSC also showed fusion temperature of the starch in the cassava bagasse around 170 °C. This value gradually reduced to 162.5 °C and 152.3 °C when the samples were hydrolyzed for twelve and twenty-four hours, respectively.
Keywords: TG; DSC; bagaço de mandioca; hidrólise enzimática; amido; TG; DSC; cassava bagasse; enzymatic hydrolysis; starch; CNPQ::ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA::ALIMENTOS